2023
DOI: 10.3390/pr11061837
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Molecular Docking, Molecular Dynamics Studies, and In Vitro Biological Evaluation of New Biofunctional Ketoprofen Derivatives with Different N-Containing Heterocycles

Stanimir Manolov,
Dimitar Bojilov,
Iliyan Ivanov
et al.

Abstract: Herein, we report the synthesis of four new hybrid molecules between ketoprofen or 2-(3-benzoylphenyl)propanoic acid and N-containing heterocyclic compounds, such as piperidine, pyrrolidine, 1,2,3,4-tetrahydroquinoline, and 1,2,3,4-tetrahydroisoquinoline. The obtained hybrid compounds were fully characterized using 1H- and 13C-NMR, UV-Vis, and HRMS spectra. Detailed HRMS analysis is provided for all novel hybrid molecules. The compounds were assessed for their in vitro anti-inflammatory and antioxidant activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…Nonsteroidal and steroidal anti-inflammatory drugs reduce inflammation, but these drugs have many unwanted side effects. Anti-inflammatory drugs are known to show a dose-dependent ability to inhibit thermally induced protein denaturation [68,69]. The results showed that the leaf extracts had better anti-inflammatory activity than the fruit extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Nonsteroidal and steroidal anti-inflammatory drugs reduce inflammation, but these drugs have many unwanted side effects. Anti-inflammatory drugs are known to show a dose-dependent ability to inhibit thermally induced protein denaturation [68,69]. The results showed that the leaf extracts had better anti-inflammatory activity than the fruit extracts.…”
Section: Discussionmentioning
confidence: 99%
“…The affinity of arzanol, (R)-bitalin A, and (S)-bitalin A to the human serum albumin was evaluated according to the previously reported protocol in a molecular docking study [67]. The stability of the predicted complexes between human serum albumin and the three compounds was evaluated further using a molecular dynamics study, according to the previously reported protocol [67,68].…”
Section: %I Ad =mentioning
confidence: 99%
“…The findings regarding the antibacterial activity, antioxidant effect, and toxicity experiments, as well as in silico analysis, demonstrated the potential of N-{4-[(4-bromophenyl)sulfonyl]benzoyl}-L-valine and 2-{4-[(4-bromophenyl)sulfonyl]phenyl}-4-isopropyl-4H-1,3-oxazol-5-one for the development of new antimicrobial drugs to combat Gram-positive bacteria, particularly Enterococcus faecium biofilm-associated illnesses. Manolov and co-workers [4] reported the synthesis of a series of novel compounds between ketoprofen and nitrogen-containing heterocyclic compounds (piperidine, pyrrolidine, 1,2,3,4-tetrahydroquinoline, and 1,2,3,4-tetrahydroisoquinoline). The compounds were investigated for their anti-inflammatory and antioxidant properties in vitro.…”
mentioning
confidence: 99%